Evaluation of drinking water in rural communities of the Oilfield Canto do Amaro-CPCA, RN, Brazil - Pinto Filho, Jorge Luís de Oliveira; Souza, Raquel Franco de; Petta, Reinaldo Antônio (Sustainability in Debate, 2018)
This work aimed to evaluate the supply system and water quality for human consumption of rural communities of the Oilfield Canto do Amaro (CPCA), in the state of Rio Grande do Norte (RN). The methodology consisted in identifying the supply system, evaluation of supply through environmental perception, and analysis of the physicochemical parameters and heavy metals in water. It was found that turbidity, pH, electrical conductivity, hardness, ammonia, nitrate, nitrite, calcium, magnesium and iron presented acceptable values determined by the Directive No. 2914/2011 of the Ministry of Health and Resolution No. 357/2005 of the National Council for Environment (CONAMA). As for the dissolved oxygen, it was observed that 84.61% of the samples had lower levels than allowed by CONAMA Resolution No. 357/2005. It was evident also that the oil and grease content in the samples ranged from 0.36 to 6.10 mg/L, with an average content of 1.42 mg/L, with a potential indicative of risks to human health. According to CONAMA Resolution No. 357/2005 oil and greases should be virtually absent. The amounts of Cd, Cu, Pb and Cr were all below the Limit of Detection (LOD) of the method used for analysis. Zinc concentrations ranged between 0.01 and 0.04 mg/L, with a mean of 0.01 mg/L, within the maximum amounts established by CONAMA Resolution No. 357/2005 and Directive No. 2914/2011.